SAT0489 Association of childhood overweight measures with adulthood knee cartilage defects and bone marrow lesions: a 25-year cohort study. (15th June 2017) - Meng, T; Thayer, S; Venn, A; Cicuttini, F; March, L; Dwyer, T; Halliday, A; Cross, M; Laslett, L; Jones, G; Ding, C; Antony, B
Abstract : Background: Obesity and overweight have been associated with increased risk of knee osteoarthritis (OA). Cartilage defects and bone marrow lesions (BMLs) are imaging biomarkers that predict the development and progression of knee OA. However, there are no studies describing the effect of childhood obesity or overweight on risk of adulthood knee structural abnormalities including cartilage defects and BMLs. Objectives: To describe associations between body weight, body mass index (BMI), overweight status and fat mass in childhood and knee cartilage defects and BMLs measured using magnetic resonance imaging (MRI) in adulthood 25 years later. Methods: Subjects broadly representative of the Australian population (n=327, aged 31–41 years) were selected from the Australian Schools Health and Fitness Survey of 1985 (n=8498, aged 7–15 years). Childhood measures, including weight, height and skinfolds were measured in 1985. BMI and fat mass were calculated. They underwent T1-weighted fat-suppressed and proton density-weighted fat-suppressed MRI scans 25 years later. Cartilage defects and BMLs were measured from MRI using a semi-quantitative scoring system. Log binomial regression analyses were used to determine the associations of childhood overweight measures with adulthood knee cartilage defects and BMLs. Results: There were no associations between childhood overweight measures and adulthood tibio-femoral cartilage defects; however, body weight, BMI and overweight status were positively associated with patellar cartilage defects after adjustment for childhood age, duration of follow-up, sex, childhood height (if weight or fat mass was the predictor), childhood injury, adulthood injury and corresponding adulthood measures (RR 1.05, 95% CI 1.01 to 1.09 for weight; RR 1.10, 95% CI 1.01 to 1.19 for BMI; RR 2.06, 95% CI 1.19 to 3.58 for overweight). After further adjustment for patellar BMLs, these associations remained largely unchanged and the association of fat mass with patellar cartilage defects became significant (RR 1.10, 95% CI 1.01 to 1.21). Childhood overweight measures were not associated with adulthood BMLs in either tibio-femoral or patellar compartments. However, sex-specific analyses showed BMI and overweight status were associated with higher risks of patellar BMLs after adjustment for covariates in men (RR 1.36, 95% CI 1.03 to 1.81 for BMI; RR 4.37, 95% CI 1.01 to 18.91 for overweight) but not in women. Conclusions: Childhood overweight measures were significantly associated with increased risk of patellar cartilage defects and BMLs in young adults. In addition, overweight status was significantly associated with patellar BMLs in men which may explain why overweight was only associated with increased knee pain in men as we reported earlier. These results indicate the importance of addressing overweight in childhood to aid in preventing adulthood knee structural abnormalities which increase the risk of OA in later life. Disclosure of Interest: None declared